The Impact Of Leadership Styles On Operational Efficiency In The Saudi Red Crescent Authority During The Period (2020–2025): A Systematic Review (The Review of Diabetic Studies, 2025)
Background:Effective leadership in emergency medical services (EMS) is a pivotal determinant of organizational performance, influencing decision-making accuracy, team communication, and response outcomes. Within the Saudi Red Crescent Authority (SRCA), leadership has become especially critical amid rapid digital transformation and public health crises such as the COVID-19 pandemic.Objective:This systematic review aimed to examine how different leadership styles affect operational efficiency in Saudi Red Crescent emergency services between 2020 and 2025. The review explored which leadership models—transformational, transactional, servant, authentic, or situational—most effectively enhanced performance indicators such as response time, coordination, staff engagement, and service quality.Methods:Following PRISMA 2020 guidelines, a comprehensive search was conducted in PubMed, Scopus, Web of Science, CINAHL, and Google Scholar. Eligible studies included quantitative, qualitative, and mixed-methods designs involving Saudi EMS personnel. Data extraction followed the Joanna Briggs Institute (JBI) framework, and quality appraisal used the Newcastle–Ottawa Scale, JBI, CASP, and MMAT tools. Narrative and thematic syntheses were employed to integrate findings.Results:Twenty-three studies met the inclusion criteria. Transformational leadership was the most common and consistently effective style, linked to an average 8–12 % reduction in ambulance response times and higher team morale. Servant and authentic leadership improved communication and reduced burnout, while transactional leadership maintained procedural compliance but correlated with increased fatigue. Leadership adaptability during COVID-19—particularly situational leadership—proved essential for sustaining operations under crisis. Across studies, empathetic communication, autonomy, and technological integration emerged as mediating factors connecting leadership style to operational efficiency.Conclusion:Leadership style is a decisive driver of operational performance in Saudi Red Crescent emergency services. Transformational, servant, and authentic leadership models foster resilience, collaboration, and rapid response capability, aligning closely with Vision 2030 goals for healthcare excellence. Investing in structured leadership training and human-centered management practices is essential to enhance EMS efficiency and staff well-being in the Kingdom’s evolving emergency care landscape.